(untitled) (Third Sector Social Economic Review, 2023)
Culture is one of the factors that affect the economic behavior. It is difficult to measure the effect of culture on economic behavior separately from other variables. Since controlled laboratory experiments can minimize the effect of other variables, they provide a convenient method for examining the independent effect of culture on economic behavior. An advantage of controlled laboratory experiments is that they are replicable. An experiment conducted in an experimental economics laboratory can be run in another laboratory with the same design or some modifications and with different participants. This study aims to discuss experimental studies based on ultimatum and public goods games, which are frequently used in laboratory experiments, in terms of cultural differences and to discuss the measurability of the effect of culture on economic decisions by using laboratory experiments and examine whether laboratory experiments are suitable for investigating this effect and its sources. Our examination showed that studies comparing social groups with each other display more consistent results than studies in which the same is repeated in different countries. According to the studies based on the ultimatum game and cultural differences, it is seen that religion-based differences between communities, respect for authority, partisanship, and racial discrimination have effects on the experimental results. The experimental studies based on public goods game show that social norms specific to a culture, gender and the economic system in which the participants grew up have important effects on their decisions.